Der Markt fur̈ Milch - Petra Salamon (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2001)
– (4) Driven by demand expansion and favourable prices world dairy production continued to rise and international trade in milk products slowly recovered from the consequences of the various economic crises in 1998-99. Assuming continued economic growth, demand and prices are likely to increase. Extremely low stocks and scarce market supplies of skimmed milk powder in the EU caused the Commission to reduce the level of subsidies spent on milk powder for calf raising. Butter stocks, however, remained high and EU exports failed to improve due to sluggish demand. Export subsidies on cheese were repeatedly reduced reflecting both firm demand and the weak Euro. With regard to milk production quotas, several EU member countries made special arrangements for allotting parts of the additional quotas to their producers while others introduced some kind of regulated quota exchange. The latter is expected not only to better bring together quota demand and supply but also to avoid transactions at extremely high prices.
Keywords: 330